Achieving quality performance and environmental sustainability through the genius loci of quality management systems: A study on computer accessories companies in Taiwan and Southern China. Issue 2 (25th February 2014) - Ho, Ying-Chin; Fan, Liang-Chen
Abstract : Purpose: – The purpose of this study is threefold. First, the authors will confirm the existence and the intensity of the latent "genius loci" within quality management systems. Second, the authors will confirm the extent of the genius loci with environmental sustainability. Finally, the authors will try to understand whether a quality management system's performance can be affected by its genius loci, and whether a quality management system's environmental sustainability performance can be affected by the extent of environmental sustainability in its genius loci. Design/methodology/approach: – The extent of the genius loci in quality management systems and the genius loci with environmental sustainability are tested through higher-order confirmatory factor analysis. Findings: – The findings of this study are as follows. First, genius loci partially exist in quality management systems. Second, the genius loci with the environmental sustainability concept also exist partially in certain respects. There is a lack of recognition and actions on environmental sustainability activities in organizations. The lack of recognition and actions leads to the unsatisfactory performance of quality management systems in environmental sustainability. As a result, business goals with environmental sustainability aspects cannot be fully supported and achieved. Originality/value: – The results of this study can help small- and medium-sized OEM and ODM computer accessories companies in Taiwan and Southern China to understand the level of genius loci within their quality management systems and the extent that genius loci are linked with environmental sustainability. This understanding can be beneficial to them in achieving successful quality management systems with environmental sustainability.